MODEL MATEMATIS DAN SIMULASI PERPINDAHAN PANAS PROSES PENGECORAN KONTINYU BAJA SLAB - Darmanto, Prihadi Setyo; Syahlan, Arief; Koesnohadi, Koesnohadi (Mesin, 2002)
This paper presents mathematical model and numerical simulation using CFD software FLUENT 5.4 applied on continuous casting process of steel slab. The distribution of temperature of the steel slab since it exits the mould till straightening region was evaluated. The result of numerical evaluation was also compared to the measurement temperature taken at some selected points. The comparison showed that there was a good agreement between the numerical result and the measurement data. The percentage of both liquid and solid phases along the slab was also simulated. It seems that the simulation of solid phase growth could be used as a method for determining the cross section position where the solidification ceases.